Planned surveys - Mills, Vicente (Technical bulletin / Philippines (Commonwealth). Dept. of Agricuture and Commerce, 1937)
Deals with cadastral survey carried out by the Bureau of lands of under its supervision, 1901-1937, and includes estimates of the time and cost involved in completing such surveys of the whole territory of the commonwealth.